The Utilization of Cake Application in Strengthening English Speaking Skills: Students’ Experience - Budiyanto, Darmawan; Manisah, Manisah; Ridho, M. Rasyid (Journal International Inspire Education Technology, 2024)
English is widely used as a tool to communicate people from different countries. In fulfilling this, skills in using language are needed. The purpose of this study is to find the use of the Cake application in strengthening English speaking skills of students majoring in Tadris English, semester 6, Universitas Islam Negeri Yunus Batusangkar. This research approach is to use quantitative with research design using surveys. The data collection technique was carried out using questionnaires given to each person in each class. The number of statements made in the questionnaire was 18 statements. The population used is Universitas Islam Negeri Mahmud Yunus Batusangkar students, majoring in Tadris English, semester 6. The samples used were 40 samples. The results of the assessment show that the use of the Cake application can help students improve their speaking skills. This is because of the many kinds of features available in the application, the selection of levels ranging from beginner to advanced in accordance with learning interests, equipped with assessments that can find out or correct the location of mistakes made, and are effectively used because they use the internet network and mobile phones or laptops that are already owned by students.